Physical and chemical properties of surface waters in the Różany Strumień catchment in the years 1988–2012 - Okońska, Monika; Pietrewicz, Katarzyna (Wydział Nauk Geograficznych i Geologicznych Uniwersytetu im. Adama Mickiewicza, 2017)
The Różany Strumień catchment located in the north of Poznań is an example of a small anthropogenically-induced catchment. The main aim of this study is to analyse the variability of selected physical and chemical properties of surface waters in the catchment area in the years 1988–2012. It was found that surface waters in the catchment can be classified as hard and very hard, with slightly basic pH. The deterioration of Różany Strumień water quality concerns chemical oxygen demand, conductivity, chlorides, sodium, ammonia nitrogen and nitrite nitrogen concentrations. The authors of the study have noticed a decrease in the amount of phosphates and sulphates in the water. As observed, the hydrogeochemical type of water changed from calcium-hydrogen carbonate-sulphate into calcium-sodium-hydrogen carbonate-sulphate-chloride. Changes in water chemistry are probably a result of anthropogenic impacts, and they can be associated with the transformation of land use in the catchment area, i.e. the ongoing urbanization of the area.
Keywords: Różany Strumień; urban catchment; water quality indicators; hydrochemistry